Acceptance of Allogeneic Serum Eye Drops Among Users of Autologous Serum Eye Drops—A Survey-Based Study - Frank Blaser; Mohammadjavad Abbasi; Mario D. Toro; Timothy Hamann; Daniel Barthelmes; Sandrine A. Zweifel; Martina M. Bosch; Isabelle Meneau; Jana Schneider; Sadiq Said; Vinoth Yogarasa (Journal of Clinical Medicine, 2026)
Background/Objectives: To assess the acceptance of, attitudes towards, and concerns regarding allogeneic serum eye drops (Allo-SEDs) among patients treated with autologous serum eye drops (ASEDs). Methods: We conducted this investigator-initiated, cross-sectional, single-center survey at the Department of Ophthalmology, University Hospital Zurich, Switzerland. We consecutively recruited all patients using ASEDs during routine visits, who anonymously completed a 9-item questionnaire comprising eight 11-point Likert-scale items and one open numerical item on the daily application frequency. We assessed perceived ASED effectiveness, willingness to switch to Allo-SEDs under different scenarios, and concerns regarding safety, efficacy, and immunological risks. Results: Of 202 eligible patients, 107 returned the questionnaire (53.0%). The full eligible cohort had a median (IQR) age of 63.5 (49.2–75.0) years and a median ASED treatment duration of 4.0 (1.0–8.0) years. They rated ASEDs as highly effective (median 9, IQR 8.2–10.0) and applied them a median of 7 (5–10.5) times daily. Willingness to switch was low without clinical need (median 3, IQR 0–6; p = 1.0), increased when autologous production was no longer feasible (median 7, IQR 5–9; p < 0.001), and was intermediate for general openness (median 5, IQR 2–8; p = 0.7). Concerns regarding infectious disease transmission, immunological reactions, and therapeutic efficacy correlated with lower willingness to switch (all r = −0.29 to −0.46). Daily application frequency did not correlate with acceptance. Conclusions: Patients were highly satisfied with ASEDs but were reluctant to switch to Allo-SEDs unless autologous production was no longer feasible. Among the domains assessed, concerns regarding infection, immunological reactions, and efficacy were the main barriers to acceptance, supporting targeted patient education.